The Poverty of Management Control Philosophy - Hofstede, George (Academy of Management Review, 1978)
The ineffectiveness of many management control systems is attributed to the cybernetic philosophy on which they are based. A distinction is made between routine industrial-type processes, for which a homeostatic paradigm is more suitable, and non-routine, non-industrial-type processes, for which a political paradigm is recommended. Attempts at enforcing a cybernetic paradigm on the latter processes, like Program-Planning-Budgeting System and Management-By-Objectives, are bound to fail.